Representasi Gender pada Buku Ajar Al-‘Arabiyyah Baina Yadaik Terbitan Arab Saudi - Ainurrofiq, Faiq; Ahmad Mujib (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Textbooks can be one of the means to construct gender roles. Therefore, gender discrimination and equality can be produced and perpetuated through textbooks. This paper wants to examine the construction of the representation of the roles of men and women and the social context surrounding the writing of the textbook al-'Arabiyyah baina Yadaik published in Saudi Arabia. The researcher uses critical discourse analysis to track the representation of the gender division of women and men. Text construction and visualization of male and female roles are analyzed at the macro, meso, and microstructure levels. In the end, the researcher concluded: First, the division of gender roles in the al-'Arabiyyah baina Yadaik textbook is represented in a discriminatory manner. Male gender roles are described as very dominant compared to female roles. The dominance of men over the relationship can be seen at the level of visualization, their role in the family realm, their role in public work, sports activities, and physical activities. Second, the discriminatory depiction of gender roles in the textbook al-'Arabiyyah baina Yadaik is inseparable from the author's social cognition, which is dominantly influenced by the fatwas of Salafi scholars of Saudi Arabia who domesticate the role of women. The access and dominance of strong Salafi scholars in organizing the realm of education in Saudi Arabia affect the construction of discriminatory gender roles, including at the level of textbook preparation. Abstrak Buku ajar dapat menjadi salah satu sarana untuk mengkonstruksi peran gender. Oleh karena itu, diskriminasi dan kesetaraan gender dapat diproduksi dan dilanggengkan melalui buku ajar. Tulisan ini hendak mengkaji konstruksi representasi peran laki-laki dan perempuan dan konteks sosial yang melingkupi penulisan buku ajar al-‘Arabiyyah baina Yadaik yang diterbitkan di Arab Saudi. Peneliti menggunakan analisis wacana kritis dalam melacak bentuk-bentuk representasi pembagian peran gender perempuan dan laki-laki. Kontruksi teks dan visualisasi peran laki-laki dan perempuan dianalisa pada level struktur makro, meso, dan mikro. Pada akhirnya peneliti menyimpulkan: Pertama, pembagian peran gender dalam buku ajar al-‘Arabiyyah baina Yadaik direpresentasikan secara diskriminatif. Peran gender laki-laki digambarkan sangat dominan dibandingkan dengan peran perempuan. Dominasi laki-laki atas perepuan tampak pada tataran visualisasinya, perannya dalam ranah keluarga, perannya dalam pekerjaan publik, aktifitas olah raga, dan aktifitas fisik. Kedua, penggambaran diskriminatif peran gender dalam buku ajar al-‘Arabiyyah baina Yadaik tidak terlepas dari relasi kognisi sosial penulis yang secara dominan dipengaruhi oleh fatwa-fatwa ulama Salafi Arab Saudi yang mendomestifikasi peran perempuan. Akses dan dominasi ulama Salafi yang kuat dalam menata ranah pendidikan di Arab Saudi berpengaruh dalam konstruksi peran gender yang diskriminatif termasuk pada tataran penyusunan buku ajar.